2016
DOI: 10.1371/journal.pone.0157085
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27 Prevents Atherosclerosis by Suppressing Lipoprotein Lipase-Induced Lipid Accumulation and Inflammatory Response in Apolipoprotein E Knockout Mice

Abstract: Atherosclerotic lesions are lipometabolic disorder characterized by chronic progressive inflammation in arterial walls. Previous studies have shown that macrophage-derived lipoprotein lipase (LPL) might be a key factor that promotes atherosclerosis by accelerating lipid accumulation and proinflammatory cytokine secretion. Increasing evidence indicates that microRNA-27 (miR-27) has beneficial effects on lipid metabolism and inflammatory response. However, it has not been fully understood whether miR-27 affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 51 publications
4
37
0
1
Order By: Relevance
“…Consistent with our findings, administration of miR-27a mimic in Apoe -/mice diminished lipid levels in both plasma and peritoneal macrophages, thereby alleviating atherosclerosis by targeting macrophage-derived lipoprotein lipase (Lpl) [48]. Of note, HITS-CLIP experiments revealed that miR-27a also targeted microsomal triglyceride transfer protein (Mttp), a crucial chaperone involved in lipoprotein production [49].…”
Section: Role Of Mir-27a In Global Regulation Of Cholesterol Homeostasupporting
confidence: 85%
“…Consistent with our findings, administration of miR-27a mimic in Apoe -/mice diminished lipid levels in both plasma and peritoneal macrophages, thereby alleviating atherosclerosis by targeting macrophage-derived lipoprotein lipase (Lpl) [48]. Of note, HITS-CLIP experiments revealed that miR-27a also targeted microsomal triglyceride transfer protein (Mttp), a crucial chaperone involved in lipoprotein production [49].…”
Section: Role Of Mir-27a In Global Regulation Of Cholesterol Homeostasupporting
confidence: 85%
“…It is reported that miR‐27 can inhibit the expression of inflammatory factors, such as scavenger receptors associated with lipid uptake, and decreased aortic plaque size in ApoE knockout mice. Additionality, miR‐27 overexpression can reduce lipid accumulation via the downregulation of macrophage‐derived lipoprotein lipase (LPL) expression . Interestingly, in other studies, miR‐27a can decrease the level of the LDL receptors that are important for efficient endocytosis of the LDL receptor‐LDL‐C complex .…”
Section: Preclinical Studies Of Mirnas In Atherosclerosismentioning
confidence: 99%
“…miR-758-5p reduces macrophage oxLDL uptake by directly inhibiting expression of the scavenger receptor CD36 [76]. miR-27a/b regulates macrophage cholesterol homeostasis by targeting genes involved in cholesterol uptake (LOX-1 and CD36) and efflux (ABCA1) [77]. miR-23a-5p and miR-212 increase foam cell formation by reducing cholesterol efflux from macrophages through ABCA1 [31,78].…”
Section: Monocyte Recruitment Macrophage Differentiation and Foam Cementioning
confidence: 99%
“…miR-34 increases the binding capacity of oxLDL to macrophages by facilitating bridging between lipoprotein lipase (LPL) and LOX-1 [79]. Conversely, miR-27 and miR-590 inhibit LPL expression to prevent macrophage lipid accumulation and cytokine release [77,80,81].…”
Section: Monocyte Recruitment Macrophage Differentiation and Foam Cementioning
confidence: 99%